Citrinin Derivatives From Penicillium Citrinum Y34 That Inhibit α-Glucosidase and ATP-Citrate Lyase - Chen, Shanji; Tian, Danmei; Wei, Jihua; Li, Cong; Ma, Yihan; Gou, Xiaoshuang; Shen, Yiran; Chen, Mei; Zhang, Sihao; Li, Jia; Wu, Bin; Tang, Jinshan (Frontiers in Marine Science, 2022)
Two new citrinin dimers bearing a rare 6,6-spiroketal moiety (1 and 2) and four known analogues (3-6), together with 18 known citrinin monomers (7-24), were isolated from the culture of hydrothermal vent associated fungus Penicillium citrinum Y34. Their structures were identified by extensive spectroscopic analyses, 13C NMR calculation in combination with DP4+, linear correlation coefcient (R2) and MAE values analyses, and ECD calculation. The α-glucosidase and ATP-citrate lyase (ACL) inhibitory activities of isolated compounds were evaluated. Compounds 1, 3 and 12 displayed moderate α-glucosidase inhibitory activities with IC50 values of 239.8, 176.2, and 424.4 μM, respectively. Enzyme kinetics investigations of 1 and 3 suggested their noncompetitive inhibition of α-glucosidase with Ki values of 204.3 and 212.7 μM, respectively. Meanwhile, compound 4 showed significant ACL inhibitory potential with an IC50 value of 17.4 μM. Furthermore, the interactions of 1, 3 and 12 with α-glucosidase and 4 with ACL were investigated by molecular docking assay. This study demonstrates that citrinins, especially for their dimers, could be potential lead compounds for the development of new agents for the treatment of metabolic diseases.